2021
DOI: 10.1080/0886022x.2021.1949350
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal transport status and first episode of peritonitis: a large cohort study

Abstract: Background: Peritonitis is one of the most serious complications of peritoneal dialysis (PD). This study aimed to explore the relationship between peritoneal transport status and the first episode of peritonitis, as well as the prognosis of patients undergoing continuous ambulatory peritoneal dialysis (CAPD). Method: A retrospective cohort study was conducted, analyzing data of CAPD patients from 1st January 2009, to 31st December 2017. Baseline data within 3 months after PD catheter placement was recorded. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Previous reports indicate that peritoneal injury triggers the activation of inflammatory cells, such as neutrophils, macrophages, and mesothelial cells, which recognize bacterial pathogens via Toll-like receptors (TLRs), activate relative inflammatory signaling pathways, and ultimately release a large number of pro-inflammatory cytokines ( 27 – 29 ). It is also suggested that higher PSTR may predispose patients to more inflammation than lower PSTR ( 30 ). Among the differentially expressed proteins between the groups, we identified three proteins (ITGB2, S100A8, and GP96) with a fold change ≥1.9 for their possible participation in the immune inflammatory response according to GO and KEGG analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports indicate that peritoneal injury triggers the activation of inflammatory cells, such as neutrophils, macrophages, and mesothelial cells, which recognize bacterial pathogens via Toll-like receptors (TLRs), activate relative inflammatory signaling pathways, and ultimately release a large number of pro-inflammatory cytokines ( 27 – 29 ). It is also suggested that higher PSTR may predispose patients to more inflammation than lower PSTR ( 30 ). Among the differentially expressed proteins between the groups, we identified three proteins (ITGB2, S100A8, and GP96) with a fold change ≥1.9 for their possible participation in the immune inflammatory response according to GO and KEGG analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, high peritoneal transport status is a well-known PD-related peritonitis risk factor [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…However, hypoalbuminemia was recently reported to correlate with poor prognosis in PD patients and was attributed more to inflammation than malnutrition ( 19 ). A sufficient amount of albumin is likely to improve intravascular volume and bind inflammatory cytokine, all of which are risk factors for the incidence of PD related peritonitis, resulting in technique failure of PD and increased hophitalization rate and mortality ( 20 , 21 ). Second, with regard to ALP, it is evidently related to nutritional status and inflammation in CKD ( 22 , 23 ) and may be further involved in the progression of vascular calcification.…”
Section: Discussionmentioning
confidence: 99%